Intraoperative Use of Angiotensin II for Severe Vasodilatory Shock During Liver Transplantation: A Case Report. Issue 2 (11th February 2021) - Running, Kati; Weinberg, Devin; Trudo, William; Sullivan, Cinnamon L.; Patel, Gaurav P.
Abstract : Refractory hypotension is a known entity in liver transplantation. Catecholamine and vasopressin infusions are first-line therapies. There has been recent interest in angiotensin II (Ang-2) as an alternative vasopressor; however, liver failure patients were excluded from the original trials. Ang-2 has potential in this patient population. This case discusses a patient who received an infusion of Ang-2 during a liver transplant for combined liver failure–induced distributive shock and septic shock. It is the first known successful use of intraoperative Ang-2 in this situation, and it shows that Ang-2 may be safe in liver transplantation when traditional therapies fail.